Electrifying discourse: Anodal tDCS of the primary motor cortex selectively reduces action appraisal in naturalistic narratives. (November 2020) - Birba, Agustina; Vitale, Francesca; Padrón, Iván; Dottori, Martín; de Vega, Manuel; Zimerman, Máximo; Sedeño, Lucas; Ibáñez, Agustín; García, Adolfo M.
Abstract: Non-invasive stimulation of the primary motor cortex (M1) modulates processing of decontextualized action words and sentences (i.e., verbal units denoting bodily motion). This suggests that language comprehension hinges on brain circuits mediating the bodily experiences evoked by verbal material. Yet, despite its relevance to constrain mechanistic language models, such a finding fails to reveal whether and how relevant circuits operate in the face of full-blown, everyday texts. Using a novel naturalistic discourse paradigm, we examined whether direct modulation of M1 excitability influences the grasping of narrated actions. Following random group assignment, participants received anodal transcranial direct current stimulation over the left M1, or sham stimulation of the same area, or anodal stimulation of the left ventrolateral prefrontal cortex. Immediately afterwards, they listened to action-laden and neutral stories and answered questions on information realized by verbs (denoting action and non-action processes) and circumstances (conveying locative or temporal details). Anodal stimulation of the left M1 selectively decreased outcomes on action-relative to non-action information –a pattern that discriminated between stimulated and sham participants with 74% accuracy. This result was particular to M1 and held irrespective of the subjects' working memory and vocabulary skills, further attesting to its specificity. Our findings suggest that offline modulation of motor-network excitability might lead to transient unavailability of putative resources needed to evoke actions in naturalistic texts, opening promising avenues for the language embodiment framework.